Impact of HIV infection on survival among women with stage I‐III breast cancer: Results from the South African breast cancer and HIV outcomes study. Issue 2 (4th March 2022) - Ayeni, Oluwatosin A.; O'Neil, Daniel S.; Pumpalova, Yoanna S.; Chen, Wenlong Carl; Nietz, Sarah; Phakathi, Boitumelo; Buccimazza, Ines; Čačala, Sharon; Stopforth, Laura W.; Farrow, Hayley A.; Mapanga, Witness; Joffe, Maureen; et al.
Abstract: In some countries of sub‐Saharan Africa, the prevalence of HIV exceeds 20%; in South Africa, 20.4% of people are living with HIV. We examined the impact of HIV infection on the overall survival (OS) of women with nonmetastatic breast cancer (BC) enrolled in the South African Breast Cancer and HIV Outcomes (SABCHO) study. We recruited women with newly diagnosed BC at six public hospitals from 1 July 2015 to 30 June 2019. Among women with stages I‐III BC, we compared those with and without HIV infection on sociodemographic, clinical, and treatment factors. We analyzed the impact of HIV on OS using multivariable Cox proportional hazard models. Of 2367 women with stages I‐III BC, 499 (21.1%) had HIV and 1868 (78.9%) did not. With a median follow‐up of 29 months, 2‐year OS was poorer among women living with HIV (WLWH) than among HIV‐uninfected women (72.4% vs 80.1%, P  < .001; adjusted hazard ratio (aHR) 1.49, 95% confidence interval (CI) = 1.22‐1.83). This finding was consistent across age groups ≥45 years and <45 years, stage I‐II BC and stage III BC, and ER/PR status (all P  < .03). Both WLWH with <50 viral load copies/mL and WLWH with ≥50 viral load copies/mL had poorer survival than HIV‐uninfected BC patients [aHR: 1.35 (1.09‐1.66) and 1.54 (1.20‐2.00), respectively], as did WLWH who had ≥200 CD4+ cells/mL at diagnosis [aHR: 1.39 (1.15‐1.67)]. Because receipt of antiretroviral therapy has become widespread, WLWH is surviving long enough to develop BC; more research is needed on the causes of their poor survival. Abstract : What's new? Breast cancer patients living with HIV are a growing population globally. Associations between HIV status and breast cancer subtype, treatment and survival, however, remain unclear. In this investigation of women with nonmetastatic breast cancer in South Africa, patients living with HIV at breast cancer diagnosis were found to be at significantly greater risk of death from any cause than non‐HIV‐infected women with breast cancer. This finding persisted after accounting for differences in age, ethnicity, cancer stage, cancer subtype and treatments received. The findings cast light on adverse impacts linked to HIV infection in nonmetastatic breast cancer patients, despite antiretroviral therapy.